2019
DOI: 10.1101/689893
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Critical slowing as a biomarker for seizure susceptibility

Abstract: words)The human brain has the capacity to rapidly change state, and in epilepsy these state changes can be catastrophic, resulting in loss of consciousness, injury and even death. Theoretical interpretations considering the brain as a dynamical system would suggest that prior to a seizure recorded brain signals may exhibit critical slowing, a warning signal preceding many critical transitions in dynamical systems. Using long-term intracranial electroencephalography (iEEG) recordings from fourteen patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 48 publications
0
22
1
Order By: Relevance
“…Comparing the circadian patterns of HFA and spike rates to seizures based on the individual patient and individual electrodes extends our knowledge of their relationships. In contrast to previous reports, 22,42,43 our study found a striking difference in circadian patterns of HFA and spike rates across electrodes within patients. This spatial variable behaviors of HFA and spike rates could help reconcile the discrepancies in the literature regarding how spikes and HFOs change prior to seizures.…”
Section: Chencontrasting
confidence: 99%
“…Comparing the circadian patterns of HFA and spike rates to seizures based on the individual patient and individual electrodes extends our knowledge of their relationships. In contrast to previous reports, 22,42,43 our study found a striking difference in circadian patterns of HFA and spike rates across electrodes within patients. This spatial variable behaviors of HFA and spike rates could help reconcile the discrepancies in the literature regarding how spikes and HFOs change prior to seizures.…”
Section: Chencontrasting
confidence: 99%
“…Similarly, physiological signals recorded from wearable devices could improve forecasts of seizure cycles by providing a continuous measure of underlying rhythms, rather than discrete samples (seizure times). We have shown that fast and slow cycles of brain activity can be measured from continuous EEG across diverse frequencies and regions of cortex 18 . These continuous cycles provided the most accurate estimate of seizure likelihood to date.…”
Section: Discussionmentioning
confidence: 99%
“…However, in eventual real‐world applications, a can be used to iteratively calibrate the forecast based on past performance. High‐ and low‐risk warning thresholds were computed using a pseudoprospective brute force optimization that maximized the time spent in low‐risk periods and number of seizures classified in high‐risk periods 18 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations